LEADERSHIP QUALITIES OF A FUTURE OFFICER AND READINESS FOR PROFESSIONAL ACTIVITY IN THE CONTEXT OF USING INNOVATIVE EDUCATIONAL METHODS - Качан, Микола Віталійович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
Under the modern conditions of social development, the significance of leadership qualities of an individual increases. The article is devoted to leadership as a topical issue of future officers’ military and professional training. Leadership, as a specific type of management relationship, is based more on the process of social interaction, assuming the presence of followers in the organization, rather than subordinates. Thus, the leader-commander-subordinate relationship inherent in traditional management is replaced by the leader-follower relationship, which is much more complex and requires a high level of interdependence among participants. The paper presents theoretical interpretations of the content of leadership and leader, the nature of leadership is compared with management itself, the concepts of leader-manager-commander-in-chief of military formation are compared, the specific features of military activity that require the presence of leadership qualities of officers are outlined. Innovative methods are recognized as a priority in educational activity for the formation of leadership characteristics and skills, acquisition of the necessary competencies of a future military specialist in both professional and communicative aspects. On the basis of personal pedagogical experience, we outline the most efficient in psychological and pedagogical organization for forming the traits of the leader in cadets - method of projects, role play, training. While using these methods psychological and pedagogical preconditions are directed, aimed at interaction, personal leadership development and developing skills of independent search work, presentation of the results of their activity, formation of analytical, critical thinking, initiative and creativity. Purposeful development of the leader of military formation with the account for the individual-psychological characteristics of the cadets; creation of a developing personality-oriented environment in training and real educational-service and extracurricular interaction (activity content, group dynamics, problems, reflexivity) provide a strong foundation for the development of leadership qualities of cadets. Active implementation of interactive forms (method of projects, workshops, role-playing games, etc.) will be also responsible for the development of leadership qualities of cadets. They can also contribute to the successful professional activity of future officers.